Makna Dalâl dalam al-Qurâan Perspektif Teori Dilâlat al-Alfâz - Fawaid, Ahmad (Mutawatir, 2013)
The interpretation methodology of Koran always has significant development. No death of interpretation, because the interpretation methodology will develop agree with throb of people civilization and language development. A matter of fact, Koran is a guidance book for man with Arabic language. For example, dalÃ¢l. Although concept of dalÃ¢l was exist at Muhammed period, but there are many distortion and wrong conclution after Muhammed, and lost of essential meaning of dalÃ¢l. Some people or some community said that dalÃ¢l is used to tought that considered wrong or deviate on right way, in other opinion they said that dalÃ¢l just for unbeliever, polytheist, immoral in law, and the others. The difference opinion is none other than different interpretation method to word of dalÃ¢l. Because of that, the writer interested to analyze dalÃ¢l with semantic method. Because the writer is conviced about semantic will give some enticement concept of dalÃ¢l.